Application of GNS3 to Study the Security of Data Exchange between Power Electronic Devices and Control Center - Ivan Nedyalkov (Computers, 2023)
This paper proposes the use of the GNS3 IP network modeling platform to study/verify whether the exchanged information between power electronic devices and a control center (Monitoring and Control Centre) is secure. For the purpose of this work, a power distribution unit (PDU) and a UPS (Uninterruptable Power Supply) that are used by internet service providers are studied. Capsa Free network analyzer and Wireshark network protocol analyzer were used as supporting tools. A working model of an IP network in GNS3 has been created through which this research has been carried out. In addition to checking whether the exchanged information is secure, a characterization of the generated traffic has been made, showing results for the generated traffic and which ports generate the most traffic. These carried-outstudies show that the exchanged information is not secure. As a way to secure the exchanged information, the use of VPN (Virtual Private Network) technology is proposed; thanks to a VPN, the exchange of information is secure. The obtained results confirm this and validate the applicability of GNS3 to test/study whether data exchange between power electronic devices and a control center is secure.